Current trends in the efficacy and safety of Semaglutide in the glycemic control of diabetic patients: A literature review (Research, Society and Development, 2024)
The aim of this article is to examine current trends in the efficacy and safety of semaglutide in glycemic control among diabetic patients, seeking theoretical foundation from databases such as SciELO, LILACS, and PubMed. Twenty-eight articles were selected over the past three years, following defined inclusion and exclusion criteria, using the PRISMA methodology. Results indicated that semaglutide led to a significant reduction in short-term blood glucose levels, with lower hemoglobin A1c values compared to other treatments. The drug's safety was widely recognized, both in its subcutaneous and oral forms, although gastrointestinal side effects such as nausea and vomiting were frequently reported. A significant highlight was the potential reduction in adverse cardiovascular events associated with semaglutide use in diabetic patients. This review emphasizes semaglutide as an effective and safe therapeutic option for glycemic control in type 2 diabetic patients, with potential additional benefits in reducing cardiovascular complications.